The Implementation of Directed Reading Thinking Activity (DRTA) Strategy in Teaching Reading Recount Text at SMAN 6 Medan - Indri Oktavani Br Bangun; Masitorwarni Siregar (RIRAI Publisher, 2023)
This research aims to find out how teachers implement DRTA strategy in teaching reading recount text for tenth grade at SMAN 6 Medan. To achieve the purpose of this study, the analyst utilized descriptive qualitative strategy. The data were amassed via observing the teaching and learning process of recount text, interview with English teacher, and video recording for how the implementation of DRTA strategy. The teacher has implemented 3 stages of using DRTA strategy in teaching reading recount text, Before Reading: predicting, While reading: silent reading, After reading: confirming predictions. But in the prediction stage, the teacher did not guide the students to activate their previous knowledge.